Pragmatics in ESL classroom: its importance in listening skills - Presotto, Leticia (BELT - Brazilian English Language Teaching Journal, 2014)
This article aims at discussing the importance of Pragmatics in ESL classroom, more specifically in listening tasks. In order to base our study, we present an overview of some pragmatic theories which relies on the notion of inference, like Grice (1975) and Sperber and Wilson (1995). Then, we discuss about the importance of Pragmatics among language teaching and listening skill. In this section, we highlight some important aspects that have to be considered in teaching a second language focusing in listening activities. Finally, we analyze the listening section of TOEFL exam. Here, we show how Pragmatics is present and its importance to the students who take this specific test.